Definitive-like erythroid cells derived from human embryonic stem cells coexpress high levels of embryonic and fetal globins with little or no adult globin - Chang, Kai-Hsin (© 2006 by The American Society of Hematology, 2006)
Human embryonic stem cells are a promising tool to study events associated with the earliest ontogenetic stages of hematopoiesis. We describe the generation of erythroid cells from hES (H1) by subsequent processing of cells present at early and late stages of embryoid body (EB) differentiation. Kinetics of hematopoietic marker emergence suggest that CD45(+) hematopoiesis peaks at late D14EB differentiation stages, although low-level CD45(-) erythroid differentiation can be seen before that stage. By morphologic criteria, hES-derived erythroid cells were of definitive type, but these cells both at mRNA and protein levels coexpressed high levels of embryonic (ε) and fetal (γ) globins, with little or no adult globin (β). This globin expression pattern was not altered by the presence or absence of fetal bovine serum, vascular endothelial growth factor, Flt3-L, or coculture with OP-9 during erythroid differentiation and was not culture time dependent. The coexpression of both embryonic and fetal globins by definitive-type erythroid cells does not faithfully mimic either yolk sac embryonic or their fetal liver counterparts. Nevertheless, the high frequency of erythroid cells coexpressing embryonic and fetal globin generated from embryonic stem cells can serve as an invaluable tool to further explore molecular mechanisms.